2020
DOI: 10.31234/osf.io/m25jr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genesis or Evolution of Gender Differences? Worldview-based Dilemmas in The Processing of Scientific Information

Abstract: Some issues that have been settled by the scientific community, such as evolution, the effectiveness of vaccinations, and the role of CO2 emissions in climate change, continue to be rejected by segments of the public. This rejection is typically driven by people's worldviews, and to date most research has found that conservatives are uniformly more likely to reject scientific findings than liberals across a number of domains. We report a large (N>1,000) preregistered study that addresses two questions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…However, this presents future research with a conundrum, because a number of studies have now aimed but failed to find rejection of scientific evidence on the left (e.g. [78][79][80]). For example, Lewandowsky et al [80] reported that vaccine-hesitancy and endorsement of alternative medicine-both anecdotally associated with a liberal worldview-were in fact more prevalent in right-wing libertarians and conservatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this presents future research with a conundrum, because a number of studies have now aimed but failed to find rejection of scientific evidence on the left (e.g. [78][79][80]). For example, Lewandowsky et al [80] reported that vaccine-hesitancy and endorsement of alternative medicine-both anecdotally associated with a liberal worldview-were in fact more prevalent in right-wing libertarians and conservatives.…”
Section: Discussionmentioning
confidence: 99%
“…[78][79][80]). For example, Lewandowsky et al [80] reported that vaccine-hesitancy and endorsement of alternative medicine-both anecdotally associated with a liberal worldview-were in fact more prevalent in right-wing libertarians and conservatives. Based on additional evidence from a task that required reasoning about scientific evidence 'dilemmas' that featured both worldview-consistent and inconsistent aspects, Lewandowsky et al concluded that partisans on both ends of the spectrum show biased processing of evidence, but that science denial was nevertheless a mainstay of the political right.…”
Section: Discussionmentioning
confidence: 99%